CMS Maize: A Tool to Reduce the Distance between GM and non‐GM Maize. (April 2016) - Bückmann, Heidrun; Thiele, Katja; Schiemann, Joachim
Summary: To limit admixture of genetically modified (GM) with non‐GM crops in the early stages of production, codes of good agricultural practice for GM crops have been developed. In addition to general measures, crop‐specific measures including the establishment of 'isolation distances' are required. The use of biological means like cytoplasmic male sterility (CMS) in maize provide more flexible isolation distances particularly in cases where GM maize requires higher levels of containment/confinement to ensure coexistence with agricultural production systems that do not cultivate GM plants. This article discusses the role of CMS where plants develop no or no vital pollen but the female fertility is not affected, as a biological means of reducing isolation requirements. Results of the PRICE project and other EU‐funded projects provide evidence that current isolation distances set by EU Member States are disproportionate for achieving admixture levels below the 0.9 per cent GM admixture threshold for labelling and may lead to unnecessary costs for farmers. Distances might be reduced or replaced by the use of GM CMS maize as it provides an efficient biological confinement tool and increases the flexibility for 'good agricultural practices of GM crop cultivation'. Abstract : To limit admixture of genetically modified (GM) with non‐GM crops in the early stages of production, codes of good agricultural practice for GM crops have been developed. In addition to general measures, crop‐specific measures including the establishment of 'isolation distances' are required. The use of biological means like cytoplasmic male sterility (CMS) in maize provide more flexible isolation distances particularly in cases where GM maize requires higher levels of containment/confinement to ensure coexistence with agricultural production systems that do not cultivate GM plants.